Exchange Strategy for Implementation Network of the Food Diversification Policy in Indonesia - ., Hartina; ., Alwi; Susanti, Gita (KnE Social Sciences, 2023)
The survival of a network organization as a policy implementer depends on the exchange of resources between network actors. Various studies have explained this exchange process, but in this study, was identified as a strategy to improve the performance of the policy. The main objective of this study is to explain the network exchange mechanism as a strategy for the implementation of the food diversification policy in Indonesia. The research method used a qualitative approach and a case study strategy to explain the exchange strategy for the food diversification policy. Data collection used is in-depth interviews and documentation. Data processing and analysis involve data reduction, presentation, and concluding. The results showed that the implementation of food diversification policies was not yet effective. This is caused by the exchange mechanism as a strategy has not been effective either. This is indicated by the exchange conditions of network actors, in the form of demand uncertainty, task complexity, asset specificity, and frequency that have not supported the effective implementation of this policy. The same social mechanisms in the form of restricted access, macro culture, collective sanctions, and reputation have not facilitated the successful implementation of this policy. Keywords: Food diversification; social mechanisms; exchange strategy